REVIEW OF INDUSTRIAL APPLICATIONS OF COMPUTATIONAL INTELLIGENCE - Frayn, Colin M. (International Journal of Computing, 2014)
Bringing cutting-edge natural computation research into industry is a challenging task, with numerous obstacles to overcome. In this paper I describe a few selected projects that we have developed at the Centre of Excellence for Research in Computational Intelligence and Applications (CERCIA) and I discuss the promising future of Computational Intelligence techniques in industry.